A cross-national comparative study between Australia and Singapore: attitudes towards television advertising - Phau, Ian (Technische Universiteit Eindhoven, 2008)
This paper aims to compare the attitudes of consumers in Australia and Singapore towards TV advertising through the replication of a study by Witkowski and Kellner (1998) conducted in Germany and America. Specifically, it investigates the possible converging or diverging television attitudes between Australia and Singapore. Further, it expands the previous study by studying the frequency of switching channels during advertising breaks. Data were collected from 192 Australian and 197 Singaporean respondents and were analysed. Some implications for marketers and advertisers are also discussed.